Significant gaps in hepatitis B vaccination in adults in Viet Nam: Important targets toward hepatitis B elimination by 2030. Issue 4 (23rd January 2023) - Kim, Thanh V.; Pham, Trang N.D.; Le, Duc H.; Dao, Diem V.B.; Phan, Loc T.B.; Le, Anh; Trang, Amy; Tang, Hong K.; Liu, Jason J.; Dao, Doan Y
Highlights: A significant unmet need for hepatitis B vaccination in adults remained in Viet Nam. More people in the young age groups should be recommended for hepatitis B vaccination. The social disparity in hepatitis B vaccination existed in various socioeconomic statuses. Hepatitis B vaccination should be recommended for the broader population to achieve elimination. Abstract: Background: Gaps in adult hepatitis B vaccination were undefined in Vietnam, a lower-middle-income country. To address these gaps, this study defined hepatitis B vaccine coverage in adults and its associated factors in Ho Chi Minh City (HCMC), Viet Nam. We also proposed interventional strategies, prioritizing gap identification to facilitate hepatitis B elimination by 2030 and beyond. Method: During 2019–2020, a multi-stage cluster serosurvey with probability proportional to size was conducted to representatively invite 20, 000 adults (18 years or older) throughout HCMC for hepatitis B screening (HBsAg, anti-HBs, and anti-HBc). Serologic results defined two dependent variables: vaccine-induced immunity (i.e., isolated anti-HBs) and susceptibility (i.e., HBV naive). Associations of dependent variables with surveyed demographics, socioeconomic statuses, behaviors, and medical history at risk for hepatitis B were evaluated using weighted Poisson regression. Results: The prevalence was 18.5% (95%CI, 17.3-20.0%) for vaccine-induced immunity and 37.7% (35.6-39.8%) for susceptibility. Even though analyses in the general population revealed a falling trend in vaccine-induced immunity prevalence from younger to older age groups, sensitivity analyses in the non-infected population (i.e., those who were both negative for HBsAg and anti-HBc) showed that younger age groups, especially those aged 30 to 50 years, had the lowest prevalence. Social inequalities existed in different ethnicities, residence areas, education levels, house ownership, and health insurance statuses. There was no significant association between vaccine-induced immunity or susceptibility and risky behaviors and medical histories. Conclusion: This study depicts a significant unmet need for hepatitis B vaccination in the general adult population in HCMC, Viet Nam. Indeed, the lack of vaccination was unevenly distributed regarding age groups, geographical areas, and socioeconomic statuses, which reveals profound social disparities. Therefore, to achieve hepatitis B elimination goals, besides the current recommendations for infants and risk-based strategies, hepatitis B vaccination should be recommended for the broader population.